2014
DOI: 10.1039/c4ra01866d
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of 4-nitrophenol catalyzed by silver nanoparticles supported on polymer micelles and vesicles

Abstract: We report the reduction of 4-nitrophenol catalyzed by silver nanoparticles supported on polymer micelles and vesicles which can significantly improve the stability, dispersibility and catalytic activity of silver nanoparticles even at one ppm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…15 Nitro compounds are water soluble aromatic pollutants which can hardly be biodegraded or self-cleaned by the environment. 3,[17][18][19][20][21][22][23] The catalytic reduction of water soluble aromatic pollutants by heterogeneous catalysts has many advantages like easy operation, clean processing, high efficiency, low cost, etc. 16 Recently, much attention has been paid to the catalytic reduction of nitro compounds via metal-based catalysts in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…15 Nitro compounds are water soluble aromatic pollutants which can hardly be biodegraded or self-cleaned by the environment. 3,[17][18][19][20][21][22][23] The catalytic reduction of water soluble aromatic pollutants by heterogeneous catalysts has many advantages like easy operation, clean processing, high efficiency, low cost, etc. 16 Recently, much attention has been paid to the catalytic reduction of nitro compounds via metal-based catalysts in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Consequently, it is desirable to explore simple and effective methods to maintain the longterm stability so as to determine the catalytic performance of AgNPs. [17][18][19][20][21] Lu et al reported on the in situ synthesis of AgNPs onto polystyrene (PS) core-poly(acrylic acid) (PAA) polyelectrolyte brush particles. [9][10][11][12] Hybrid catalysts integrated AgNPs with inorganic and organic supports have been successfully developed.…”
Section: Introductionmentioning
confidence: 99%
“…44 Therefore it is necessary to develop environment friendly and clean techniques for the removal of such pollutants from industrial waste water. [45][46][47][48][49][50][51] In this work, the catalytic activity of the Ag 3 PO 4 /CoFe 2 O 4 nanocomposite for the reduction of 4-nitrophenol (4-NP) and 2-nitrophenol (2-NP) with sodium borohydride (NaBH 4 ) was evaluated. The catalytic reduction process of 4-NP was monitored by UV-vis spectroscopy as shown in Fig.…”
Section: Catalytic Reduction Of Nitrophenols Over Ag 3 Po 4 / Cofe 2 Omentioning
confidence: 99%